Development of new copper-64 labeled rhodamine: a potential PET myocardial perfusion imaging agent - Norah AlHokbany; Ibrahim AlJammaz; Basem AlOtaibi; Yousif AlMalki; Bander AlJammaz; Subhani M. Okarvi (SpringerOpen, 2022)
Abstract Background Myocardial perfusion imaging (MPI) is one of the most commonly performed investigations in nuclear medicine procedures. Due to the longer half-life of the emerging positron emitter copper-64 and its availability from low energy cyclotron, together with its well-known coordination chemistry, we have synthesized 64Cu-labeled NOTA- and 64Cu-NOTAM-rhodamine conjugates as potential cardiac imaging agents using PET. Results 64Cu-NOTA- and 64Cu-NOTAM-rhodamine conjugates were synthesized using a traightforward and one-step simple reaction. Radiochemical yields were greater than 97% (decay corrected), with a total synthesis time of less than 25 min. Radiochemical purities were always greater than 98% as assessed by TLC and HPLC. These synthetic approaches hold considerable promise as a simple method for 64Cu-rhodamine conjugates synthesis, with high radiochemical yield and purity. Biodistribution studies in normal Fischer rats at 60 min post-injection, demonstrated significant heart uptake and a good biodistribution profile for both the radioconjugates. However, the 64Cu-NOTAM-rhodamine conjugate has shown more heart uptake (~ 10% ID/g) over the 64Cu-NOTA-rhodamine conjugate (5.6% ID/g). Conclusions These results demonstrate that these radioconjugates may be useful probes for the PET evaluation of MPI.